Seminar on marketing strategies for Islamic banks and financial institutions / BIMB Institute of Research and Training Sdn. Bhd - Mansor, Mohd Bakir (1997)
To regulate human lives Allah instituted a system of rights and responsibilities, and a system of rewards and punishments to enforce these rights and responsibilities. The true direct source of all rights that man enjoy is Allah referred to as Al-Shar'u. Another source of rights is contracts which are established through Allah's laws i.e. Islamic Law referred to as Al-Shariah.